REDESIGN BUILDING STRUCTURE RSGM UGM PROF. SOEDOMO USING FLAT SLAB METHOD WITH DROP PANELS - firmansyah, tomi (Universitas Bengkulu, 2020)
Flat slab is reinforced concrete plate construction without beam. Without using beam, the obtainable profit is to minimize concrete volume, height/floor, and structural load. Other profits are simpler and economic reinforcement, scaffolding, and formwork. In this study, structural redesign of RSGM UGM Prof. Soedomo Yogyakarta building was made by using flat slab method. The objective of this study was to find structural dimension of floor and roof plates as well as reinforcement of the RSGM UGM Prof. Soedomo Building using structural system of flat slab, dimension of structural column and drop panel as well as reinforcement of the RSGM UGM Prof. Soedomo Building using structural system of flat slab. This method was to redesign using flat slab method complying with the standard of SNI 2847-2013 and software ETABS 2017. The results of analysis and calculation of structural dimension using flat slab method showed floor plate thickness of 170 mm; roof plate thickness, 120 mm; drop panel thickness, 270 mm with drop panel width of 2000 mm in direction x and 1500 mm in direction y, as well as use of column dimension of 500 mm x 500 mm. The analysis using software ETABS 2016 showed building structure in period (T) of 1.07 seconds.Keywords: RSGM UGM Prof. Soedomo Building, Drop Panel, Flat slab.